Sri Lanka : Fifth Review Under the Extended Arrangement Under the Extended Fund Facility, Request for Waivers of Nonobservance of Performance Criteria, Extension of the Arrangement and Rephasing of Purchases-Press Release; Staff Report and Statement by the Executive Director for Sri Lanka. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper discusses Sri Lanka's Fifth Review under the Extended Arrangement under the Extended Fund Facility, Request for Waivers of Nonobservance of Performance Criteria, extension of the arrangement, and rephasing of purchases. The Central Bank of Sri Lanka maintained a tight monetary policy stance, intervening in the foreign exchange market and allowing for greater exchange rate flexibility in response to rising pressures. The Sri Lankan economy remains vulnerable to shocks, given high public debt, large refinancing needs, and low external buffers. Although domestic uncertainty remains elevated, the authorities are committed to strengthen the resilience of the economy through a strong policy mix, with prudent monetary policy, greater exchange rate flexibility, and revenue-based fiscal consolidation. Continued implementation of structural reforms is essential to support strong and inclusive growth. Efforts should focus on liberalizing trade, improving the business environment and promoting investment, strengthening governance, encouraging female and youth labor force participation, enhancing social protection, and improving crisis preparedness to natural disasters.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet